Structure and Function of von Willebrand Factor - Ruggeri, Zaverio M. (Thrombosis and Haemostasis, 1999)
The reader will find here a concise summary of established notions on the structure and function of von Willebrand factor (vWF), followed by a brief discussion of selected recent advances that illustrate how this molecule supports platelet function in hemostasis and thrombosis. A comprehensive review of the topic is beyond the scope of this chapter and may be found elsewhere.1-3